The Iliad - Hinds, Gareth, 1971- (Candlewick Press, 2019)
Presents a graphic novel adaptation of the ancient Greek poem written by Homer. Set in the final days of the Trojan War, the warrior leader Achilles calls upon the gods to help him when Agamemnon takes Achilles's captive Briseis.